PENGETAHUAN PALLIATIVE CARE PADA KELUARGA DENGAN KANKER - Fitriyanti, Dwi; Ananta Tanujiarso, Bagus; Jumatul Laely, Anna (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Cancer is a leading cause of death worldwide, accounting for nearly 10 million deaths in 2020, or nearly one in six deaths. Cancer is a chronic and/or terminal disease with various manifestations or signs depending on which body system is affected. The needs of cancer patients are not only the fulfillment or treatment of physical symptoms but also the importance of supporting psychological, social, and spiritual needs. The main support for cancer patients is the family, which plays an important role in providing care to the patient. The treatment given to cancer sufferers is palliative care. This research aims to determine the knowledge of palliative care in families with cancer. This research uses a quantitative descriptive methodology with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 120 responses. The research instrument used a knowledge-level questionnaire about palliative care. The data analysis technique used is univariate analysis. The research results showed that the majority of respondents' knowledge was in the poor category, with 47 (39.16%), 38 respondents (31.67%) with good knowledge, and 35 respondents (29.17%) with sufficient knowledge. Recommendations for further research can provide interventions to increase the knowledge of families with cancer. The ultimate goal of palliative care can be achieved, namely improving the patient's quality of life.